Influence of Visual Impairment on The Quality of Life: A Survey of Patients Reporting at The Low Vision Centre of the Eastern Regional Hospital Of Ghana - Ofeibea Amedo Angela; Adade Samuel; Yaa Koomson Nana; Appenteng Osae Eugene (Journal of Ophthalmic Science, 2016)
Our aim was to evaluate the influence of visual impairment on the quality of life of patients reporting at the low vision centre of the Eastern Regional Hospital in Koforidua. The World Health Organization Quality Of Life (WHOQOL-Bref) which assesses quality of life in four main domains was administered to two hundred and ninety four (294) patients who visited the low vision centre of the Eastern Regional Hospital, for various eye services. Additional information on patient demographics and their visual acuities were obtained. The mean quality of life scores were determined for the visually and non-visually impaired. 86(29.3%) of the participants were visually impaired (presenting vision worse than 6/18). A significant difference in mean age was realized between subjects who were visually impaired (53.7 ± 18.4) (mean ± SD) and subjects who were not visually impaired (34.3 ± 13.1) (p = 0.001). The visually impaired participants had a lower quality of life scores in all four domains of quality of life naming, environmental, physical, social and psychological with 7.5% unadjusted reduction in overall quality of life. Visual impairment is associated with significant reduction in different quality of life domains for this population. Quality of life is poorer with increasing severity of visual impairment.
Keywords: Visual impairment